1983
DOI: 10.1177/0148607183007005470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Guar Gum in Preventing the Dumping Syndrome

Abstract: The occurrence of dumping symptoms during 1 wk of use of 5 g of guar gum or placebo in meals was examined in a double-blind study in 11 patients, who had undergone gastric resection and were suffering from the dumping syndrome. The results show that guar gum prevented the dumping syndrome and increased tolerance to foods not previously tolerated in nine of the 11 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Much of the work relating to the slowing of gastric emptying by guar gum and pectin used hypertonic liquid test meals (41,47,48) and the results may not be relevant to the emptying of solid meals of dry matter (49,50). Harju et al (51,52) have used pectin and guar gum to relieve symptoms of patients with dumping syndrome. In the latter study, prolongation of the gastric emptying time for solids was noted with guar (52).…”
Section: Physiologic Effects Of Fibermentioning
confidence: 99%
“…Much of the work relating to the slowing of gastric emptying by guar gum and pectin used hypertonic liquid test meals (41,47,48) and the results may not be relevant to the emptying of solid meals of dry matter (49,50). Harju et al (51,52) have used pectin and guar gum to relieve symptoms of patients with dumping syndrome. In the latter study, prolongation of the gastric emptying time for solids was noted with guar (52).…”
Section: Physiologic Effects Of Fibermentioning
confidence: 99%
“…Such a reduction was found when guar gum was given to patients following gastric resection, to obese patients and to duodenal ulcer patients [6,[15][16][17], This supposition is supported by the findings in patients experiencing troublesome symptoms after proximal se lective vagotomy that the early phase of gastric emptying and the related increase in blood glucose concentration and decrease in plasma volume were markedly greater after 150 ml of a 50% glucose solution than in patients not showing symptoms [11]. However, there are patients with dumping syndrome with an early postprandial hy perglycemia, but there are also patients with a similar hyperglycemia without any symptoms [19].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in postprandial hyperglycemia is a result of decreased rates of digestion and absorption associated with the in creased meal viscosity. The study reported here shows that the effect of guar gum in reducing postprandial hyperglycemia in patients with intact stomachs [1][2][3] remains evident when the stomach has been completely removed, with food proceeding directly from the esoph agus to the lumen of the small intestine. Thus a reduc tion in gastric emptying rate, as described earlier [4][5][6], can not be the only explanation for the effect of guar gum in decreasing the postprandial hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypergly cemia per se may not be the cause of the symptoms. However, it has been shown that dumping symptoms are associated with abnormal postprandial changes of blood glucose concentration, e.g., after proximal selective va-gotomy [9], and can be reduced in some patients by guar gum [3,10]. The postprandial symptoms after total gas trectomy are partly also nondumping ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation